Changes in working life expectancy with disability in the Netherlands, 1992-2016 - Maaike van der Noordt; Suzan van der Pas; Theo G van Tilburg; Ardo van den Hout; Dorly JH Deeg (Nordic Association of Occupational Safety and Health (NOROSH), 2019)
OBJECTIVES: Like other western countries, the Netherlands has abolished early retirement schemes and is currently increasing the statutory retirement age. It is likely that also older workers with disabilities will be required to work longer. We examine the change in working life expectancy (WLE) with disability of older workers by comparing data from three periods: 1992-1996, 2002-2006 and 2012-2016. METHODS: Data are from the Longitudinal Aging Study Amsterdam (LASA). Respondents aged 55-65 with a paid job at baseline were included (N=1074). Disability was measured using the Global Activity Limitations Indicator (GALI). First, a continuous-time three-state survival model was created. Second, WLE with and without disability were estimated using MSM and ELECT in R. The modifying effects of gender and educational level were examined. RESULTS: Among those initially in paid employment, total WLE increased over 20 years. For example at age 58, total WLE increased from 3.7 to 5.5 years. WLE with disability at age 58 increased from 0.8 to 1.5 years. There was no difference in WLE with disability between male and female workers or low- and highly educated workers. CONCLUSIONS: Between the 1990s and the 2010s, subsequent generations of older workers with disabilities have extended their working lives. The findings emphasize the importance of workplace interventions that facilitate older workers with disabilities to maintain well-being and work ability. In addition, the question arises whether current exit routes out of the workforce are still adequate.